Генетические факторы нарушения сперматогенеза у мужчин со сниженной репродуктивной функцией - Жилкова, Е.С.; Феськов, А.М.; Безпечная, И.М.; Федота, А.М. (Фактори експериментальної еволюції організмів, 2014)
Aims. The correlation of DNA fragmentation level with classic sperm parameters, the male age and the level of immature spermatozoa and sperm aneuploidies was investigated. Methods. The level of the sperm DNA fragmentation was measured by the method of sperm chromatin dispersion. Semen aneuploidies were detected by the method of fluorescence in situ hybridization. The level of immature spermatozoa was measured by hyaluron binding assay. Results. There is a negative correlation between the DNA fragmentation level and sperm motility and sperm morphology. The significant negative correlation between DNA fragmentation level and immature spermatozoa level is proved. There is a negative correlation between the levels of DNA fragmentation and sperm aneuploidies. Conclusions. The failures of sperm DNA compactization influence on classic sperm parameters and correlates with the level of aneuploidies. There is a dependence of DNA fragmentation level on the male age. The critical clinically significant age for DNA fragmentation is 30 years old.